2018
DOI: 10.1186/s12885-018-4716-8
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal liver metastases: surgery versus thermal ablation (COLLISION) – a phase III single-blind prospective randomized controlled trial

Abstract: BackgroundRadiofrequency ablation (RFA) and microwave ablation (MWA) are widely accepted techniques to eliminate small unresectable colorectal liver metastases (CRLM). Although previous studies labelled thermal ablation inferior to surgical resection, the apparent selection bias when comparing patients with unresectable disease to surgical candidates, the superior safety profile, and the competitive overall survival results for the more recent reports mandate the setup of a randomized controlled trial. The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
123
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 62 publications
0
123
0
2
Order By: Relevance
“…There are several ablative technologies available, including heat radiofrequency (RF) or microwaves (MW), cold (cryoablation) or electric pulses (irreversible electroporation [IRE]) [36] ( Table 1). The common factor among ablation therapies is that they are less invasive than surgery, have a shorter recovery time and have fewer major complications [37]. RF, MW ablation, and more recently stereotactic body radiation therapy (SBRT) [38] are ablation therapies with minimal toxicity and good clinical results, providing an opportunity for curative intent to nonoperative patients.…”
Section: Unfit Patients (Fig 1b)mentioning
confidence: 99%
“…There are several ablative technologies available, including heat radiofrequency (RF) or microwaves (MW), cold (cryoablation) or electric pulses (irreversible electroporation [IRE]) [36] ( Table 1). The common factor among ablation therapies is that they are less invasive than surgery, have a shorter recovery time and have fewer major complications [37]. RF, MW ablation, and more recently stereotactic body radiation therapy (SBRT) [38] are ablation therapies with minimal toxicity and good clinical results, providing an opportunity for curative intent to nonoperative patients.…”
Section: Unfit Patients (Fig 1b)mentioning
confidence: 99%
“…[36][37][38] This has inspired an ongoing phase III randomized controlled trial comparing surgical resection to RFA for isolated colorectal liver metastases ≤ 3 cm in size. 39 This study challenges the ideology that surgical resection is the preferred management for isolated hepatic metastases, and mirrors the current treatment approaches to hepatocellular cancer, which have shifted away from surgical management of small tumors.…”
Section: Radiofrequency Ablationmentioning
confidence: 91%
“…Several studies have reported similar recurrence and survival patterns for patients with bilateral or hepatic colorectal metastases who undergo combined surgical resection and RFA compared with surgical resection alone . This has inspired an ongoing phase III randomized controlled trial comparing surgical resection to RFA for isolated colorectal liver metastases ≤ 3 cm in size . This study challenges the ideology that surgical resection is the preferred management for isolated hepatic metastases, and mirrors the current treatment approaches to hepatocellular cancer, which have shifted away from surgical management of small tumors.…”
Section: Ablative Therapiesmentioning
confidence: 99%
“…24 Therefore, the ongoing first phase III single blind prospective randomized controlled trial seeking to demonstrate noninferiority of TA compared with hepatic resection for resectable/ablatable CLM is underway. 25 If the trial is successful demonstrating reduced postprocedural morbidity and mortality, reduced length of hospital stay, and potentially decreased costs without compromising oncological outcome, ablation may change the landscape in the management of CLM and in particular for the subgroup of patients with small volume disease that can undergo ablation.…”
Section: Thermal Ablationmentioning
confidence: 99%